2017
DOI: 10.1007/s10554-017-1086-2
|View full text |Cite
|
Sign up to set email alerts
|

Intravascular ultrasound guidance of percutaneous coronary intervention in ostial chronic total occlusions: a description of the technique and procedural results

Abstract: Inability to cross the lesion with a guidewire is the most common reason for failure in percutaneous revascularization (PCI) of chronic total occlusions (CTOs). An ostial or stumpless CTO is an acknowledged challenge for CTO recanalization due to difficulty in successful wiring. IVUS imaging provides the opportunity to visualize the occluded vessel and to aid guidewire advancement. We review the value of this technique in a single-centre experience of CTO PCI. This series involves 22 patients who underwent CTO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 26 publications
0
10
0
Order By: Relevance
“…In a series involving 22 patients who underwent CTO-PCI using IVUS guidance for stumpless ostial CTO, successful outcome was achieved in 17 cases (77.3%), while no complications related with the use of IVUS were noticed [15]. Interestingly, When the success rates were analyzed taking into account the date of adoption of this technique, the learning curve had no significant impact on CTO PCI success.…”
Section: Discussionmentioning
confidence: 97%
“…In a series involving 22 patients who underwent CTO-PCI using IVUS guidance for stumpless ostial CTO, successful outcome was achieved in 17 cases (77.3%), while no complications related with the use of IVUS were noticed [15]. Interestingly, When the success rates were analyzed taking into account the date of adoption of this technique, the learning curve had no significant impact on CTO PCI success.…”
Section: Discussionmentioning
confidence: 97%
“…It has been demonstrated that IVUS-guided CTO intervention improved clinical outcomes and might reduce the rate of 12-month major adverse cardiac events when compared with angiography-guided CTO intervention [12, 13]. IVUS images provide information about lesion morphology and contribute to successful procedural results in CTO lesions [12, 14, 15], such as by helping to resolve the ambiguity of the proximal cap [16], facilitating reentry into the true lumen after subintimal crossing [1719], and helping to find the entry point of the stump [20, 21]. Two catheter types have been used in clinical practice: rotating transducer catheters and electronic array catheters.…”
Section: Discussionmentioning
confidence: 99%
“…The most frequent cause of failure in CTO recanalization is inability of the guide wire to cross the lesion [58]. In a single center series of IVUS-guided stumpless wiring of CTOs, Ryan et al [58] reported a success rate of 77% of cases and no major complications requiring intervention. IVUS has been proposed as a safe and effective tool in guiding the reverse CART approach.…”
Section: Chronic Total Occlusions (Cto)mentioning
confidence: 99%